Remote Teaching Instruction Through The Lens of Physical Education Teachers: Challenges During The Covid-19 Pandemic - Ompoc, Harlyn Mae S. (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2023)
The COVID-19 pandemic, with its widespread transmission, has profoundly impacted the world. It led to millions falling ill, and a significant loss of lives. This unprecedented crisis resulted in global measures like school closures, home quarantine, and social distancing, compelling educators and employees to embrace remote work and technology. In Physical Education (PE), characterized by its hands-on approach, teachers faced the challenge of adapting to remote instruction without adequate training. While research on quality in-person PE instruction is well-established, there is still much to uncover about remote PE instruction. This study delves into teachers' experiences during remote learning amidst the COVID-19 pandemic. Adopting a qualitative methodology, the study utilized an interview guide as the primary tool and applied a constant comparative approach for data analysis. Ten participants specializing in Physical Education, drawn from various colleges and universities in the southern Philippines, were purposefully selected for the study. Despite some having prior blended learning training, they faced challenges, including concerns about the authenticity of students’ work, connectivity issues, assessing output, quality challenges, feedback delays, and difficulties in motor skill acquisition. The findings underscore the need for targeted training programs addressing these challenges, emphasizing the importance of ongoing support and professional development for PE educators navigating remote learning environments.